Aplikasi Metode De Novo Programming untuk Optimasi Perencanaan Produksi - erni yusnita (Universitas Medan Area, 2019)
UD. Akbar Jaya is a company engaged in the bakery industry. In carrying out a production UD. Akbar Jaya often has problems with product incompatibility with the number of requests and use of resources that have not been optimal. This is considered a waste by the company, the reason is that production planning is not optimal. With this problem, optimal production planning is needed. The de novo programming method is used to obtain optimal solutions in planning production and to obtain maximum benefits. In this study production optimization has one goal, namely, maximizing profits, with existing constraints such as constraints in the availability of raw materials, budget constraints, constraints of production capacity, and constraints of demand. The results of this study indicate the optimal amount of production that must be produced by UD. Akbar Jaya and the benefits obtained for 12 periods are as many as 14985 bread products, 9969 chocolate bread products, 4128 cappucino bread products, 1151 strawberry bread products, and the maximum profit the company gets is Rp. 7,558,250